The U.S. Ecosystem‐Based Fisheries Management Policy and Road Map: Assessing Progress and Applying Lessons Learned - Chris J. Harvey; Yvonne L. deReynier; Wendy E. Morrison; Jennifer L. Cudney; Dorothy M. Dick; Travis Ford; Karla Gore; Jamison M. Gove; Elliott L. Hazen; Jerome M. Hermsen; Keith Kamikawa; Mandy Karnauskas; et al. (Fish and Fisheries, 2025)
The need for ecosystem‐based fisheries management (EBFM) is growing more urgent as environmental changes, species shifts, new ocean uses, and other factors force oceans toward novel states. In the United States, the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA Fisheries) developed an EBFM Policy in 2016, accompanied by a Road Map of 49 action items, to support marine ecosystem‐based management and conservation of fisheries, habitats, and protected species under U.S. federal jurisdiction. In 2024, NOAA Fisheries updated its EBFM Policy and Road Map and formed a team of science and policy experts to review progress and derive lessons learned during the first Road Map iteration. Four key lessons emerged: (1) progress toward EBFM in the U.S. has been substantial; (2) greater coordination could further enhance progress; (3) more effort is required to link science to management activities; and (4) human dimensions need greater integration throughout EBFM implementation. Enabling factors for progress on the Road Map included: champions at both the leadership and staff levels; use of participatory processes; motivation driven by ecosystem shocks and threats; and leveraging existing processes and frameworks. The updated EBFM Road Map supports historic and ongoing efforts to implement U.S. laws through improved coordination, integration, and knowledge exchange and can help to address many urgent challenges facing U.S. marine fisheries, habitats, and protected resources.

The business case for ecosystem-based management - Jason S. Link; Janne B. Haugen (Marine Policy, 2025)

Cumulative trophic curves elucidate tropical coral reef ecosystems - Jason S. Link; Fabio Pranovi; Matteo Zucchetta; Tye L. Kindinger; Adel Heenan; Kisei R. Tanaka (Frontiers in Marine Science, 2024)
There are few generalizable patterns in ecology, with widespread observations and predictability. One possible generalizable pattern is the cumulative trophic theory, which consistently exhibits S-curves of cumulative biomass over trophic level (TL) for over 200 different marine ecosystems. But whether those cumulative biomass patterns persist in some of the more distinct marine ecosystems, coral reefs, is unclear. Coral reefs are unique among marine ecosystems, representing global biodiversity hotspots and providing crucial ecosystem services. They are subject to many pressures, including both global (e.g., climate and ocean changes, warming, acidification) and local (e.g., overexploitation/overfishing, increase in turbidity, bleaching, habitat destruction, invasive species) stressors. The analysis of emergent ecosystem features, such as cumulative biomass S-curves, could represent a useful and new analytical option that can also be implemented for coral reefs. The cumulative biomass approach was applied to 42 U.S. Pacific islands (Guam and the Commonwealth of Northern Mariana Islands, American Samoa, the Pacific Remote Islands Areas, and the Northwestern and Main Hawaiian Islands), using data collected from fish surveys. Results show that coral reef ecosystems do indeed follow the S-curve patterns expected from cumulative trophic theory, which is not trivial for tropical reef systems that tend to be less widely examined and strongly dominated by structuring organisms like corals. The curve parameters results are also consistent with both fish assemblage diversity indexes and the benthic substrate ratio, which suggests this measure could serve as a useful ecosystem indicator to measure the ecological status of reefs. Moreover, the curve shape was consistent with what one would expect for different levels of perturbation, with the areas more densely inhabited showing less pronounced S-curves, in contrast to those observed in low human population density islands. All this is reflected in the curve parameters, particularly inflection point of the TL and steepness, generally showing a negative response to both natural and anthropogenic disturbances. Cross-archipelago differences have also been detected with the Hawaiian Island chain tending to have lower inflection points for biomass and TL than other regions. Collectively our findings demonstrate the potential application of the cumulative biomass approach to evaluate coral reef ecosystems.

Burning trees in frozen soil: Simulating fire, vegetation, soil, and hydrology in the boreal forests of Alaska - Melissa S. Lucash; Adrienne M. Marshall; Shelby A. Weiss; John W. McNabb; Dmitry J. Nicolsky; Gerald N. Flerchinger; Timothy E. Link; Jason G. Vogel; Robert M. Scheller; Rose Z. Abramoff; Vladimir E. Romanovsky (Ecological Modelling, 2023)

Towards vibrant fish populations and sustainable fisheries that benefit all: learning from the last 30 years to inform the next 30 years - Steven J. Cooke; Elizabeth A. Fulton; Warwick H. H. Sauer; Abigail J. Lynch; Jason S. Link; Aaron A. Koning; Joykrushna Jena; Luiz G. M. Silva; Alison J. King; Rachel Kelly; Matthew Osborne; Julia Nakamura; et al. (Reviews in Fish Biology and Fisheries, 2023)

It is past time to use ecosystem models tactically to support ecosystem‐based fisheries management: Case studies using Ecopath with Ecosim in an operational management context - J. Kevin Craig; Jason S. Link (Fish and Fisheries, 2023)
The implementation of ecosystem management requires ecosystem modelling within the context of a natural resource management process. Ecopath with Ecosim (EwE) is the most widely used modelling platform for investigating the dynamics of marine ecosystems, but has played a limited role in fisheries management and in multi‐sector resource decision‐making. We review 10 case studies that demonstrate the use of EwE to support operational resource management. EwE models are being used to inform tactical decision‐making in fisheries and other ocean use sectors, as well as to identify key trade‐offs, develop appropriate policy objectives, and reconcile conflicting legislative mandates in a variety of ecosystems. We suggest the following criteria to enhance the use of EwE and other ecosystem models in operational resource management: (1) a clear management objective that can be addressed through modelling; (2) an important trade‐off and a receptive policy context amenable to trade‐off evaluation; (3) an accessible and well‐documented model that follows best practices; (4) early and iterative engagement among scientists, stakeholders, and managers; (5) integration within a collaborative management process; (6) a multi‐model approach; and (7) a rigorous review process. Our review suggests that existing management frameworks are as much or more of a limitation to the operational use of EwE than technical issues related to data availability and model uncertainty. Ecosystem models are increasingly needed to facilitate more effective and transparent decision‐making. We assert that the requisite conditions currently exist for enhanced strategic and tactical use of EwE to support fisheries and natural resource management.

Exploring ecosystem‐based management in the North Atlantic - Mark Dickey‐Collas; Jason S. Link; Paul Snelgrove; J. Murray Roberts; M. Robin Anderson; Ellen Kenchington; Alida Bundy; Margaret M. (Peg) Brady; Rebecca L. Shuford; Howard Townsend; Anna Rindorf; Murray A. Rudd; et al. (Journal of Fish Biology, 2022)
The United States, the EU and Canada established a trilateral working group on the ecosystem approach to ocean health and stressors under the Atlantic Ocean Research Alliance. Recognizing the Atlantic Ocean as a shared resource and responsibility, the working group sought to advance understanding of the Atlantic Ocean and its dynamic systems to improve ocean health, enhance ocean stewardship and promote the sustainable use and management of its resources. This included consideration of multiple ocean‐use sectors such as fishing, shipping, tourism and offshore energy. The working group met for 4 years and worked through eight steps that covered the development of common language as a basis for collaboration, challenges of stakeholder engagement, review of the governance mandates, exploring the links between sectors and ecosystems effects, identifying gaps in knowledge and uptake of science, identification of tools for ecosystem‐based management, customary best practice for tool development and communication of key research priorities. The key findings were that ecosystem‐based management enables new benefits and opportunities, and that we need to make the business case. Further findings were that adequate mandates and effective tools exist for ecosystem‐based management, and that ecosystem‐based management urgently requires integration of human dimensions, so we must diversify the conversation. In addition, it was found that stakeholders do not see their stake in ecosystem‐based management, so greater engagement with stakeholders and targeting of ocean literacy is required and a sustainable future requires a sustained investment in ecosystem‐based management, so long‐term commitment is key.

Management Strategy Evaluation: Allowing the Light on the Hill to Illuminate More Than One Species - Isaac C. Kaplan; Sarah K. Gaichas; Christine C. Stawitz; Patrick D. Lynch; Kristin N. Marshall; Jonathan J. Deroba; Michelle Masi; Jon K. T. Brodziak; Kerim Y. Aydin; Kirstin Holsman; Howard Townsend; Desiree Tommasi; et al. (Frontiers in Marine Science, 2021)
Management strategy evaluation (MSE) is a simulation approach that serves as a “light on the hill” ( Smith, 1994 ) to test options for marine management, monitoring, and assessment against simulated ecosystem and fishery dynamics, including uncertainty in ecological and fishery processes and observations. MSE has become a key method to evaluate trade-offs between management objectives and to communicate with decision makers. Here we describe how and why MSE is continuing to grow from a single species approach to one relevant to multi-species and ecosystem-based management. In particular, different ecosystem modeling approaches can fit within the MSE process to meet particular natural resource management needs. We present four case studies that illustrate how MSE is expanding to include ecosystem considerations and ecosystem models as ‘operating models’ (i.e., virtual test worlds), to simulate monitoring, assessment, and harvest control rules, and to evaluate tradeoffs via performance metrics. We highlight United States case studies related to fisheries regulations and climate, which support NOAA’s policy goals related to the Ecosystem Based Fishery Roadmap and Climate Science Strategy but vary in the complexity of population, ecosystem, and assessment representation. We emphasize methods, tool development, and lessons learned that are relevant beyond the United States, and the additional benefits relative to single-species MSE approaches.

Changing how we approach fisheries: A first attempt at an operational framework for ecosystem approaches to fisheries management - Jason S. Link; Geir Huse; Sarah Gaichas; Anthony R. Marshak (Fish and Fisheries, 2020)
The increasing need to account for the many factors that influence fish population dynamics, particularly those external to the population, has led to repeated calls for an ecosystem approach to fisheries management (EAFM). Yet systematically and clearly addressing these factors, and hence implementing EAFM, has suffered from a lack of clear operational guidance. Here, we propose 13 main factors (shift in location, migration route or timing, overfishing (three types), decrease in physiology, increase in predation, increase in competition, decrease in prey availability, increase in disease or parasites and a decline in habitat quality or habitat quantity) that can negatively influence fish populations via mechanisms readily observable in ~20 population features. Using these features as part of a diagnostic framework, we develop flow charts that link probable mechanism(s) underlying population change to the most judicious management actions. We then apply the framework for example case studies that have well‐known and documented population dynamics. To our knowledge, this is the first attempt to provide a clearly defined matrix of all the probable responses to the most common factors influencing fish populations, and to examine possible diagnostics simultaneously, comparatively and relatively in an attempt to elucidate the most probable mechanisms responsible. The framework we propose aims to operationalize EAFM, thereby not only better diagnosing factors influencing fish populations, but also suggesting the most appropriate management interventions, and ultimately leading to improved fisheries. We assert the framework proposed should result in both better use of limited analytical and observational resources and more tailored and effective management actions.

Cumulative biomass curves describe past and present conditions of Large Marine Ecosystems - Fabio Pranovi; Simone Libralato; Matteo Zucchetta; Marco Anelli Monti; Jason S. Link (Global Change Biology, 2020)
Implementing the Ecosystem Approach in marine ecosystems is moving from preliminary steps—dedicated to defining the optimal features for indicators and developing efficient indicator frameworks—towards an operational phase where multisector marine management decisions are executed using this information. Within this operational context, emergent ecosystem properties are becoming quite promising as they have been demonstrated to be globally widespread and repeatable, and to be quite effective in detecting significant state variations of complex systems. Biomass accumulation across TLs (CumB‐TL) combines two important emergent properties of an ecosystem (energy flow, in terms of transfer efficiency, and storage, expressed as biomass), both amenable to detecting rapid ecosystem change. However, for further application, it is crucial to understand which types of drivers an indicator is sensitive to and how robust it is in relation to modifications of the external conditions and/or the system state. Here we address some outstanding questions of these CumB‐TL curves related to their sensitivity to various drivers by carrying out a global scale assessment (using data from 62 LMEs) over six decades (1950–2010). We confirm the consistency of the S‐pattern across all the LMEs, independent from latitude, ecosystem, environmental conditions, and stress level. The dynamics of the curve shape showed a tendency to stretch (i.e. decrease of steepness), in the presence of external disturbance and conversely to increase in steepness and shift towards higher TL in the case of recovery from stressed conditions. Our results suggest the presence of three main types of ecosystem dynamics, those showing an almost continuous increase in ecological state over time, those showing a continuous decrease in ecological state over time, and finally those showing a mixed behaviour flipping between recovering and degrading phases. These robust patterns suggest that the CumB‐TL curve approach has some useful properties for use in further advancing the implementation of the Ecosystem Approach, allowing us to detect the state of a given marine ecosystem based on the dynamics of its curve shape, by using readily available time series data. The value of being able to identify conditions that might require management actions is quite high and, in many respects, represents the main objective in the context of an Ecosystem Approach, with large applications for detecting and responding to global changes in marine ecosystems.

Better Together: The Uses of Ecological and Socio-Economic Indicators With End-to-End Models in Marine Ecosystem Based Management - Jamie C. Tam; Gavin Fay; Jason S. Link (Frontiers in Marine Science, 2019)

Economic and Ecosystem Effects of Fishing on the Northeast US Shelf - Gavin Fay; Geret DePiper; Scott Steinback; Robert J. Gamble; Jason S. Link (Frontiers in Marine Science, 2019)

Characterizing and comparing marine fisheries ecosystems in the United States: determinants of success in moving toward ecosystem-based fisheries management - Jason S. Link; Anthony R. Marshak (Reviews in Fish Biology and Fisheries, 2019)

Ocean Ecosystem-Based Management Mandates and Implementation in the North Atlantic - Murray A. Rudd; Mark Dickey-Collas; Johanna Ferretti; Ellen Johannesen; Nicol M. Macdonald; Richard McLaughlin; Margaret Rae; Torsten Thiele; Jason S. Link (Frontiers in Marine Science, 2018)

Ocean Futures Under Ocean Acidification, Marine Protection, and Changing Fishing Pressures Explored Using a Worldwide Suite of Ecosystem Models - Erik Olsen; Isaac C. Kaplan; Cameron Ainsworth; Gavin Fay; Sarah Gaichas; Robert Gamble; Raphael Girardin; Cecilie H. Eide; Thomas F. Ihde; Hem Nalini Morzaria-Luna; Kelli F. Johnson; Marie Savina-Rolland; et al. (Frontiers in Marine Science, 2018)

Comparing Apples to Oranges: Common Trends and Thresholds in Anthropogenic and Environmental Pressures across Multiple Marine Ecosystems - Jamie C. Tam; Jason S. Link; Scott I. Large; Kelly Andrews; Kevin D. Friedland; Jamison Gove; Elliott Hazen; Kirstin Holsman; Mandy Karnauskas; Jameal F. Samhouri; Rebecca Shuford; Nick Tomilieri; et al. (Frontiers in Marine Science, 2017)

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Bloom or bust: synchrony in jellyfish abundance, fish consumption, benthic scavenger abundance, and environmental drivers across a continental shelf - Brian E. Smith; Michael D. Ford; Jason S. Link (Fisheries Oceanography, 2016)
Increases in gelatinous zooplankton ( GZ ) populations, their dominance of some ecosystems, their impacts to other taxa, and their questionable trophic value remain global concerns, but they are difficult to quantify. We compared trends in GZ abundance from direct sampling for the northeast U.S. continental shelf and tested their association with GZ consumption by spiny dogfish ( Squalus acanthias ); the abundance of two benthic scavengers: Atlantic hagfish ( Myxine glutinosa ) and grenadiers (Family: Macrouridae); and four environmental indices: Atlantic Multidecadal Oscillation, North Atlantic Oscillation, and sea surface and bottom temperatures. Defined as scyphozoans, siphonophores, ctenophores, and salps, the abundance of GZ on the shelf has oscillated with blooms approximately every 10–15 yr. Conservative estimates of annual removal of GZ by spiny dogfish ranged from approximately 0.3–298 g individual −1 with spiny dogfish being the primary GZ feeder sampled on the shelf. The examination of three abundance series for GZ identified one shelf‐wide trend and strong relationships with 2‐yr lagged consumption and scavenger abundance (namely hagfish), and sea surface temperature. With multimodel inference, these covariates led to an optimal model of GZ abundance. Blooms of GZ abundance on this shelf were influenced by environmental change, provide surges of food for spiny dogfish, and may offer ‘food falls’ for scavenging fishes. The bioenergetic tradeoffs of consuming greater amounts of GZ compared to other major prey (e.g., fishes) remain unknown; however, these surges of food in the northwest Atlantic appear to be important for fishes, including support for benthic scavenger productivity.

A Proposal for Fishery Habitat Conservation Decision-Support Indicators - Terra Lederhouse; Jason S. Link (Coastal Management, 2016)

Which design elements of individual quota fisheries help to achieve management objectives? - Michael C Melnychuk; Timothy E Essington; Trevor A Branch; Selina S Heppell; Olaf P Jensen; Jason S Link; Steven J D Martell; Ana M Parma; Anthony D M Smith (Fish and Fisheries, 2016)
Individual quota (IQ) management systems in commercial marine fisheries are highly diverse, differing in the security, durability and exclusivity of the harvesting privilege and the transferability of quota units. This diversity in the degree of harvest rights may influence the effectiveness of IQ fisheries to meet management objectives. We conducted a global meta‐analysis of 167 stocks managed under IQs to test whether the strength of harvest rights impacts the conservation status of stocks in terms of catch, exploitation rate and biomass relative to management targets. We used non‐parametric methods to assess non‐linear relationships and linear regression models to explicitly consider interactions among predictors. Most IQ fisheries consistently met fleet‐wide quota limits (94% of stocks had recent catches below or within 10% of quotas), but only 2/3 of IQ fisheries adhered to sustainable management targets for biomass and exploitation rate (68% of stocks had exploitation rates below or within 10% of targets and 63% of stocks had biomass above or within 10% of biomass targets). Strikingly, when exclusivity of the harvesting privilege was low, exploitation rates depended on whether IQ implementation was industry‐driven (exploitation below targets) or government‐mandated (exploitation above targets). At high levels of exclusivity, exploitation rates converged to just below management targets. Transferability of quota units was associated with stock biomass closer to and slightly above target levels than stocks with non‐transferable quota. However, regional differences had the strongest effect on biomass, suggesting that other management or biological attributes of regional fishery systems have greater influence on marine populations.

Relating Mandates in the United States for Managing the Ocean to Ecosystem Goods and Services Demonstrates Broad but Varied Coverage - Christy M. Foran; Jason S. Link; Wesley S. Patrick; Leah Sharpe; Matthew D. Wood; Igor Linkov (Frontiers in Marine Science, 2016)

Can catch share fisheries better track management targets? - Michael C Melnychuk; Timothy E Essington; Trevor A Branch; Selina S Heppell; Olaf P Jensen; Jason S Link; Steven J D Martell; Ana M Parma; John G Pope; Anthony D M Smith (Fish and Fisheries, 2012)
Fisheries management based on catch shares – divisions of annual fleet‐wide quotas among individuals or groups – has been strongly supported for their economic benefits, but biological consequences have not been rigorously quantified. We used a global meta‐analysis of 345 stocks to assess whether fisheries under catch shares were more likely to track management targets set for sustainable harvest than fisheries managed only by fleet‐wide quota caps or effort controls. We examined three ratios: catch‐to‐quota, current exploitation rate to target exploitation rate and current biomass to target biomass. For each, we calculated the mean response, variation around the target and the frequency of undesirable outcomes with respect to these targets. Regional effects were stronger than any other explanatory variable we examined. After accounting for region, we found the effects of catch shares primarily on catch‐to‐quota ratios: these ratios were less variable over time than in other fisheries. Over‐exploitation occurred in only 9% of stocks under catch shares compared to 13% of stocks under fleet‐wide quota caps. Additionally, over‐exploitation occurred in 41% of stocks under effort controls, suggesting a substantial benefit of quota caps alone. In contrast, there was no evidence for a response in the biomass of exploited populations because of either fleet‐wide quota caps or individual catch shares. Thus, for many fisheries, management controls improve under catch shares in terms of reduced variation in catch around quota targets, but ecological benefits in terms of increased biomass may not be realized by catch shares alone.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Lessons in modelling and management of marine ecosystems: the Atlantis experience - Elizabeth A Fulton; Jason S Link; Isaac C Kaplan; Marie Savina‐Rolland; Penelope Johnson; Cameron Ainsworth; Peter Horne; Rebecca Gorton; Robert J Gamble; Anthony D M Smith; David C Smith (Fish and Fisheries, 2011)
Models are key tools for integrating a wide range of system information in a common framework. Attempts to model exploited marine ecosystems can increase understanding of system dynamics; identify major processes, drivers and responses; highlight major gaps in knowledge; and provide a mechanism to ‘road test’ management strategies before implementing them in reality. The Atlantis modelling framework has been used in these roles for a decade and is regularly being modified and applied to new questions (e.g. it is being coupled to climate, biophysical and economic models to help consider climate change impacts, monitoring schemes and multiple use management). This study describes some common lessons learned from its implementation, particularly in regard to when these tools are most effective and the likely form of best practices for ecosystem‐based management (EBM). Most importantly, it highlighted that no single management lever is sufficient to address the many trade‐offs associated with EBM and that the mix of measures needed to successfully implement EBM will differ between systems and will change through time. Although it is doubtful that any single management action will be based solely on Atlantis, this modelling approach continues to provide important insights for managers when making natural resource management decisions.

Ecosystem‐based fisheries management in the Northwest Atlantic - Jason S Link; Alida Bundy; William J Overholtz; Nancy Shackell; John Manderson; Daniel Duplisea; Jon Hare; Mariano Koen‐Alonso; Kevin D Friedland (Fish and Fisheries, 2011)
The northwest Atlantic has had a notable history of living marine resource (LMR) exploitation. There have been calls for evaluating and improving approaches to manage those resources as stocks have undergone sequential depletion, with some dramatic instances of stock declines. The need for more holistic ecosystem‐based approaches to manage LMRs has been increasingly recognized as part of these calls, along with the recognition that there are broader issues to consider when managing a fishery. We discuss some of the major efforts to this end which are extant among our institutions. We emphasize current initiatives to implement ecosystem‐based fisheries management in the northwest Atlantic, with a focus on how advice based on the natural sciences supports an ecosystem‐based approach. We present this information as a case study within a rich historical context of fisheries science and management.

Trophic role of Atlantic cod in the ecosystem - Jason S. Link; Bjarte Bogstad; Henrik Sparholt; George R. Lilly (Fish and Fisheries, 2009)
As the world’s oceans continue to undergo drastic changes, understanding the role of key species therein will become increasingly important. To explore the role of Atlantic cod ( Gadus morhua Gadidae) in the ecosystem, we reviewed biological interactions between cod and its prey, predators and competitors within six ecosystems taken from a broad geographic range: three are cod‐capelin ( Mallotus villosus Osmeridae) systems towards cod’s northern Atlantic limit (Barents Sea, Iceland and Newfoundland–Labrador), two are more diverse systems towards the southern end of the range (North Sea and Georges Bank–Gulf of Maine), and one is a species‐poor system with an unusual physical and biotic environment (Baltic Sea). We attempt a synthesis of the role of cod in these six ecosystems and speculate on how it might change in response to a variety of influences, particularly climate change, in a fashion that may apply to a wide range of species. We find cod prey, predators and competitors functionally similar in all six ecosystems. Conversely, we estimate different magnitudes for the role of cod in an ecosystem, with consequently different effects on cod, their prey and predator populations. Fishing has generally diminished the ecological role of cod. What remains unclear is how additional climate variability will alter cod stocks, and thus its role in the ecosystem.

Timber Harvest Impacts on Water Yield in the Continental/Maritime Hydroclimatic Region of the United States - Jason A. Hubbart; Timothy E. Link; John A. Gravelle; William J. Elliot (Forest Science, 2007)
The inland Pacific Northwest of the United States is influenced by both maritime and continental hydrometeorogical conditions. To date there are limited studies of hydrologic impacts resulting from contemporary timber harvest in this region. Streamflow data were collected since 1991 at the Mica Creek Experimental Watershed (MCEW) in northern Idaho. Treatments were designed to isolate the effects of road construction and two different harvest practices (50% clearcut, 50% partial cut). The change in water yield was assessed using linear regression and analysis of covariance (ANCOVA). Water yield increased in excess of 270 mm/yr (P < 0.01) after clearcut harvesting, and by more than 140 mm/yr (P < 0.01) after partial cut harvesting. Monthly and seasonal analyses revealed the largest impacts of harvest practices on water yield during the snow deposition and melt season from November through June. Dry season analyses (July through October) indicated negligible water yield increases after treatments. Estimates of evapotranspiration (ET) as the residual of the catchment water balance suggest that ET was reduced by 35% and 14% after clearcut and partial cut harvest, respectively. These results establish a base on which to develop tools for effective watershed management in the northern Idaho continental/maritime hydroclimatic region.

Autopsy your dead…and living: a proposal for fisheries science, fisheries management and fisheries - Tim D. Smith; Jason S. Link (Fish and Fisheries, 2005)
Ghoti papers Ghoti aims to serve as a forum for stimulating and pertinent ideas. Ghoti publishes succinct commentary and opinion that addresses important areas in fish and fisheries science. Ghoti contributions will be innovative and have a perspective that may lead to fresh and productive insight of concepts, issues and research agendas. All Ghoti contributions will be selected by the editors and peer reviewed. Etymology of Ghoti George Bernard Shaw (1856‐1950), polymath, playwright, Nobel prize winner, and the most prolific letter writer in history, was an advocate of English spelling reform. He was reportedly fond of pointing out its absurdities by proving that ‘fish’ could be spelt ‘ghoti’. That is: ‘gh’ as in ‘rough’, ‘o’ as in ‘women’ and ‘ti’ as in palatial. Abstract Concerns abound about the state of the world's fisheries, and by association fisheries science and fisheries management. An important question is the cause of the problems with fisheries, which are managed based on advice given by practioners of the discipline of fisheries science. These scientists provide advice in two distinct forms, one ‘policy supporting’ and the other ‘policy forming’. Policy supporting advice is given within an existing management setting and is typically provided only after rigorous and standardized evaluation. In contrast, there is no formal basis for evaluating policy‐forming advice. Criteria for evaluating the adequacy of policy forming advice are difficult to define, and the absence of such criteria poses difficulties for both fisheries scientists and managers. Following a medical practice analogy, we propose rigorously conducting ‘autopsies’ of fisheries as an approach for evaluating policy‐forming advice. A systematic approach to conducting such autopsies is suggested, with the recognition that this may be crucial for the further development of fisheries science as a scientific discipline rather than as an art form.

Spatial distribution and overlap between ichthyoplankton and pelagic fish and squids on the southern flank of Georges Bank - Lance P. Garrison; William Michaels; Jason S. Link; Michael J. Fogarty (Fisheries Oceanography, 2002)
We conducted larval and adult fish surveys on the southern flank of Georges Bank during the spring of two years (1990 and 1995) with contrasting physical conditions. We employed canonical correspondence analysis (CCA) to examine the relationships between physical variables and the spatial distribution of pelagic fish and ichthyoplankton. Surface temperature bottom temperature, and vertical stratification were significant factors affecting larval fish distributions, and there were groups of species with similar responses to these variables. There were also consistent relationships between physical variables and pelagic fish and squid abundances and spatial distributions. Pelagic fish and ichthyoplankton with similar responses to hydrographic variables had high spatial overlap, and variation in hydrographic regimes modulated the strength of this interaction. Pelagic fish and squids are potentially important predators of both larval and juvenile fish on Georges Bank. Hydrographic structure modulates the degree of spatial overlap and therefore likely influences the strength of predator–prey interactions.

The Rhesus monkey immunoglobulin IGHD and IGHJ germline repertoire - Jason M. Link; Matthew A. Hellinger; Harry W. Schroeder (Immunogenetics, 2002)

Models of predation and fishing mortality in aquatic ecosystems - Stuart J Whipple; Jason S Link; Lance P Garrison; Michael J Fogarty (Fish and Fisheries, 2000)
The dynamics of fish stocks are greatly influenced by predatory and fishery removals. We describe the strengths and weaknesses of a suite of approaches that assess the scope and magnitude of fishery and predatory mortality in aquatic ecosystems. We examine: (i) empirical models for pattern detection, process exploration, and model parameterization (e.g. multispecies time series and multiple regression); (ii) qualitative process‐based models of species interactions (e.g. food web analyses and loop analyses); and quantitative process‐based multispecies models that include: (iii) static flow models (e.g. Ecopath ); (iv) dynamic models of either numerical abundance (e.g. Lotka–Volterra) or biomass (e.g. Ecosim and multispecies biomass dynamics); and (v) spatially explicit versions of the above. Decisions concerning a specific modelling approach should be evaluated in the context of the goals of the model and empirical database. Important considerations include model use, desired output, and management context. Four important factors to consider in model selection are the spatial and temporal extent and resolution, conservation of mass or numbers, mathematical representation of predator–prey interactions, and mathematical representation of technical interactions. We conclude that the most effective modelling exercise to achieve a given set of goals should incorporate the evaluation of multiple model configurations.

Dynamics of lake herring (Coregonus artedi) reactive volume for different crustacean zooplankton - Jason Link (Hydrobiologia, 1998)